(untitled) (Agricultural Engineering, 2016)
The objective of the paper was to determine the impact of the rotational screw speed and the level of moisture of raw material on the efficiency and energy consumption of the extrusion-cooking process. Measurement of the extrusion-cooking process efficiency (Q) was carried out through determination of the extrudates mass and energy consumption was determined with the use of a specific mechanical energy (SME). Based on the research results it was found out that the factor which significantly decides on the measured values was a rotational screw speed. Along with the increase of this parameter the energy consumption and extrusion-cooking process efficiency increased during processing of corn grits. Extrusion-cooking process efficiency depended also on the level of moisture of raw material. At lower moisture of raw material the efficiency decreased along with the increase of the screw speed and above 18% of the moisture level it increased. Reverse relation was reported during testing the energy consumption of the extrusion-cooking process.